Evidence for clinical safety, efficacy, and parent and physician perceptions of levocetirizine for the treatment of children with allergic disease - Pampura, A. N.; Papadopoulos, N. G.; Spičák, V.; Kurzawa, R. (Int Arch Allergy Immunol, 2011)
Allergic rhinitis (AR) and chronic idiopathic urticaria (CIU) are highly burdensome diseases, which are increasing in prevalence, especially in the paediatric population. Despite the availability of a large number of medications for treatment of AR and CIU, their use in children has primarily been based on data obtained from a limited number of clinical trials in children and/or testing in adults. The H(1)-antihistamines have traditionally been used as first-line treatment for the relief of both AR and CIU symptoms in children. The first-generation H(1)-antihistamines are associated with marked adverse effects such as sedation, sleepiness/drowsiness as well as difficulties in learning and cognitive processing; thus, they are recommended for limited or discontinued use in children with AR or CIU. In contrast, second-generation H(1)-antihistamines are more adapted for the use in children with AR and CIU due to better safety profiles. However, only a limited number of trials with these agents have been conducted and generally, data from well-designed trials in children are lacking. Levocetirizine is one of the most extensively investigated H(1)-antihistamines for its pharmacologic properties, safety, efficacy as well as overall global satisfaction in children aged 2-12 years. Levocetirizine is the only H(1)-antihistamine launched in the 21st century shown to lack clinically relevant adverse effects on physical and psychomotor development or routine laboratory tests over a long-term period of 18 months in 1- to 3-year-old children predisposed to development of allergic disease. Available data suggest that levocetirizine is a suitable treatment option for AR and CIU in children aged 6 months to 12 years.
Keywords: Adult Anti-Allergic Agents Attitude of Health Personnel Cetirizine Child Child; Allergic; Non-Sedating Humans Infant Parents Physicians Randomized Controlled Trials as Topic Rhinitis; Perennial Rhinitis; Preschool Chronic Disease Histamine H1 Antagonists; Seasonal Treatment Outcome Urticaria